Electrode and preparation method and application thereof

By using a nickel substrate and a coated metal layer in the electrode, combining high-entropy alloys and metal nickel, and increasing the specific surface area by etching the grooves, the problem of low catalytic activity of the electrolytic water catalyst is solved, achieving more efficient water electrolysis reactions and electrode stability.

CN119685864AActive Publication Date: 2025-03-25HUANENG YIMIN COAL POWER CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411792310.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Existing electrolytic water catalysts have the problem of low catalytic activity, especially in terms of exposure of catalytic reactive sites in high entropy alloys.

Method used

An electrode is adopted, which includes a nickel substrate and a metal layer coated on the surface of the nickel substrate. The material of the metal layer includes metal nickel and a high entropy alloy. A multiple etching grooves are distributed on the surface of the metal layer, and the coverage of the etching grooves is 50 to 100%. The electrodes are prepared by plasma spraying and pulsed laser etching to form a dense and high specific surface area metal layer.

Benefits of technology

By increasing the specific surface area of ​​the electrode and providing more active sites, the catalytic activity of the electrode is improved, the bubble formation and mass transfer process is optimized, the efficiency of water electrolysis is improved, and the long-term stable performance of the electrode is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685864A_ABST
    Figure CN119685864A_ABST
Patent Text Reader

Abstract

The invention provides an electrode and a preparation method and application thereof. The electrode comprises a nickel base material and a metal layer wrapping the surface of the nickel base material, materials of the metal layer comprise metal nickel and high-entropy alloy, a plurality of etching grooves are distributed in the surface, away from the nickel base material, of the metal layer, and the coverage degree of the etching grooves in the surface of the metal layer is 50-100%. The existence of the etched grooves on the surface of the metal layer is beneficial for increasing the specific surface area of the electrode, and more active sites are provided for water electrolysis reaction. The high-entropy alloy has rich active sites due to the unique lattice structure, and the number of the active sites is further increased due to the existence of the etching grooves, so that the catalytic activity of the electrode is improved. And the etched groove structure is beneficial to formation and separation of hydrogen and oxygen bubbles, so that the residence time of the bubbles on the surface of the electrode is shortened, and the mass transfer process of the bubbles is optimized, thereby being beneficial to improving the water electrolysis efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water electrolysis, and in particular to an electrode and a preparation method and application thereof. Background Art

[0002] Driven by renewable electricity, water electrolysis is expected to become an ideal long-term hydrogen production method to achieve "zero carbon" emissions. Compared with traditional alloys, high entropy alloys can provide more catalytic active sites due to their unique structural characteristics, including lattice distortion and long-range lattice disorder, and therefore have broad application prospects in the field of water electrolysis catalysts. Since the formation of high entropy alloys often requires high-temperature calcination, it is difficult to form the high surface area pore structure required for the catalytic reaction in this process, which limits the exposure of the intrinsic high-activity catalytic reaction active sites and is not conducive to the improvement of catalytic reaction activity. In addition, compared with the Raney nickel-type electrodes widely used in alkaline water electrolysis, there is currently a lack of large-scale processing methods that can effectively integrate high entropy alloys to meet industrial applications. Summary of the invention

[0003] The main purpose of the present invention is to provide an electrode and a preparation method and application thereof, so as to solve the problem of low catalytic activity of water electrolysis catalyst in the prior art.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, an electrode is provided, which includes a nickel substrate and a metal layer coated on the surface of the nickel substrate, the material of the metal layer includes metallic nickel and a high entropy alloy, and a plurality of etched grooves are distributed on the surface of the metal layer away from the nickel substrate, and the coverage of the etched grooves on the surface of the metal layer is 50 to 100%.

[0005] Furthermore, the width of the above-mentioned etching groove is 20-50nm, and the depth is 1-20nm; and / or, the spacing between adjacent etching grooves is 10-50nm; and / or, the plurality of etching grooves are distributed in an array; and / or, the surface of the metal layer also contains hydroxyl groups, and the hydroxyl density in the total surface of the metal layer is 4-20OH / nm 2 ; and / or, the thickness of the metal layer is 20 to 100 μm; and / or, the mass ratio of the metal nickel to the high entropy alloy is 10 to 100:100; and / or, the specific surface area of ​​the electrode is 40 to 180 m 2 / g.

[0006] Furthermore, the elements in the above-mentioned high entropy alloy are selected from any five or more of titanium, vanadium, chromium, manganese, nickel, iron, cobalt, copper, zinc, molybdenum, ruthenium, rhodium, palladium, osmium, iridium and platinum.

[0007] According to another aspect of the present invention, a method for preparing the aforementioned electrode is provided, and the preparation method comprises: step S1, smelting and atomizing a high entropy alloy raw material in sequence to obtain a high entropy alloy powder; step S2, mixing the high entropy alloy powder with metal nickel powder to obtain a metal mixture; step S3, coating the metal mixture on the surface of a nickel substrate by plasma spraying to obtain a composite material; step S4, etching the surface of the composite material with a pulsed laser to form a metal layer on the surface of the nickel substrate, thereby obtaining an electrode.

[0008] Furthermore, in the above step S1, the smelting time is 2 to 12 hours; and / or the smelting temperature is 1500 to 2500°C; preferably, the smelting is carried out in a vacuum suspension smelting furnace; the power of the vacuum suspension smelting furnace is 50 to 500kW; and / or the vacuum leakage rate of the vacuum suspension smelting furnace is <1Pa / h; and / or the particle size of the high entropy alloy powder is 100 to 500 mesh; and / or the morphology of the high entropy alloy powder is an ellipsoid.

[0009] Furthermore, in the above step S2, the mixing is ball milling mixing, and the rotation speed of the ball milling mixing is 150 to 500 rpm; and / or, the ball milling mixing time is 0.5 to 10 h; and / or, the particle size of the metal nickel powder is 300 to 500 meshes.

[0010] Furthermore, in the above step S3, the power of plasma spraying is 30 to 65 kW; and / or, the gas for plasma spraying is H2 / Ar mixed gas, and the volume ratio of hydrogen to argon in the H2 / Ar mixed gas is 1:2 to 10; and / or, the flow rate of the H2 / Ar mixed gas is 8 to 15 L / min; preferably, the plasma spraying is vacuum plasma spraying.

[0011] Furthermore, in the above step S4, the power density of the pulsed laser is 5 to 100 J / cm 2 ; and / or, the wavelength of the pulse laser is 100 to 1200 nm; and / or, the frequency of the pulse laser is 5 to 100 kHz; and / or, the pulse width of the pulse laser is 10 to 2000 fs; and / or, the output laser power of the pulse laser is 1000 to 10000 mW.

[0012] Furthermore, the above step S4 also includes placing the etched composite material in a saturated water vapor environment for hydroxylation treatment to obtain an electrode; preferably, the temperature of the hydroxylation treatment is 10 to 60° C.; and / or, the time of the hydroxylation treatment is 0.5 to 10 hours; and / or, the protective gas in the saturated water vapor environment is selected from any one or more of nitrogen, argon and helium; and / or, the mass content of oxygen in the saturated water vapor environment is less than 0.1%.

[0013] According to another aspect of the present invention, there is provided use of the aforementioned electrode in electrolysis of water.

[0014] By applying the technical solution of the present invention, the presence of the etched grooves on the surface of the metal layer helps to increase the specific surface area of ​​the electrode, providing more active sites for the electrolysis of water reaction. High entropy alloys have abundant active sites due to their unique lattice structure, and the presence of the etched grooves further increases the number of these active sites, thereby helping to improve the catalytic activity of the electrode. In addition, the etched groove structure is conducive to the formation and detachment of hydrogen and oxygen bubbles, reduces the residence time of bubbles on the electrode surface, optimizes the mass transfer process of bubbles, thereby helping to improve the efficiency of water electrolysis. The presence of metallic nickel not only helps to improve the bonding force between the metal layer and the nickel substrate, but also makes the metal layer more compact, helps to reduce the shedding of the metal layer during the electrolysis process, and improves the long-term stability of the electrode. Controlling the coverage of the etched grooves on the surface of the metal layer within the above range helps to further increase the catalytic active sites on the electrode surface while maintaining the stability of the electrode structure, thereby helping to improve the catalytic activity of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0016] Figure 1 A SEM image of the electrode in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0018] Terminology explanation: High entropy alloy refers to an alloy composed of five or more main elements, with the atomic fraction of each element usually greater than 5% and less than 35%, and these elements form an alloy with approximately equal molar ratios.

[0019] As analyzed in the background technology of this application, the catalyst for water electrolysis in the prior art has the problem of low catalytic activity. In order to solve the above problem, this application provides an electrode and a preparation method and application thereof.

[0020] In a typical embodiment of the present application, an electrode is provided, which includes a nickel substrate and a metal layer coated on the surface of the nickel substrate, the material of the metal layer includes metallic nickel and a high entropy alloy, and a plurality of etched grooves are distributed on the surface of the metal layer away from the nickel substrate, and the coverage of the etched grooves on the surface of the metal layer is 50 to 100%.

[0021] The presence of etched grooves on the surface of the metal layer helps to increase the specific surface area of ​​the electrode and provide more active sites for the electrolysis of water. High entropy alloys have abundant active sites due to their unique lattice structure, and the presence of etched grooves further increases the number of these active sites, thereby helping to improve the catalytic activity of the electrode. In addition, the etched groove structure is conducive to the formation and detachment of hydrogen and oxygen bubbles, reduces the residence time of bubbles on the electrode surface, and optimizes the mass transfer process of bubbles, thereby helping to improve the efficiency of water electrolysis. The presence of metallic nickel not only helps to improve the bonding force between the metal layer and the nickel substrate, but also makes the metal layer more compact, which helps to reduce the shedding of the metal layer during the electrolysis process and improves the long-term stability of the electrode. Controlling the coverage of the etched grooves on the surface of the metal layer within the above range helps to further increase the catalytic active sites on the electrode surface while maintaining the stability of the electrode structure, thereby helping to improve the catalytic activity of the electrode.

[0022] In one embodiment of the present application, the width of the above-mentioned etching groove is 20-50nm and the depth is 1-20nm; and / or, the spacing between adjacent etching grooves is 10-50nm; and / or, multiple etching grooves are distributed in an array; and / or, the surface of the metal layer also contains hydroxyl groups, and the hydroxyl density in the total surface of the metal layer is 4-20OH / nm 2 ; and / or, the thickness of the metal layer is 20 to 100 μm; and / or, the mass ratio of the metal nickel to the high entropy alloy is 10 to 100:100; and / or, the specific surface area of ​​the electrode is 40 to 180 m 2 / g.

[0023] Smaller etching groove width and depth can increase the effective surface area of ​​the electrode, provide more catalytic active sites, thereby accelerating the electrochemical reaction rate. At the same time, the appropriate etching groove size helps to promote the formation and detachment of gas (hydrogen, oxygen) bubbles, reduce the residence time of gas on the electrode surface, optimize the bubble mass transfer process, and further improve the catalytic efficiency of the electrode. However, if the etching groove width and depth are too small, the circulation of the electrolyte may be hindered, the flow resistance is increased, and it is not conducive to the reaction. It is preferred to control the width and depth of the etching groove within the above range to help improve the efficiency of electrolysis of water. The electrode rich in hydroxyl groups on the surface can better attract and maintain the contact of the electrolyte, especially when the electrode is immersed in an electrolyte environment, the hydrophilic surface helps the uniform distribution and rapid penetration of the electrolyte, and helps to optimize the charge transfer process of the electrode-electrolyte interface. In addition, the presence of hydroxyl groups can stabilize the active metal sites of the electrode, help reduce the probability of metal sites being oxidized in the air, and help to keep the electrode catalytically active for a long time. Too high a hydroxyl density may cause changes in the physical properties of the electrode surface, affecting its mechanical strength and stability. Therefore, controlling the density of hydroxyl groups in the metal layer within the above range can help further improve the catalytic activity of the electrode. The presence of metallic nickel helps to reduce the resistance of the metal layer and improve the charge transfer efficiency. At the same time, metallic nickel acts as a binder, which helps to improve the structural stability of the electrode. Excessive metallic nickel may dilute the active sites of the high entropy alloy and reduce the catalytic efficiency of the electrode. Therefore, controlling the mass ratio of metallic nickel to the high entropy alloy within the above range can help further improve the electrolysis efficiency of the electrode.

[0024] In order to further improve the catalytic activity of the electrode, in one embodiment of the present application, the elements of the high entropy alloy are preferably selected from any five or more of titanium, vanadium, chromium, manganese, nickel, iron, cobalt, copper, zinc, molybdenum, ruthenium, rhodium, palladium, osmium, iridium, and platinum.

[0025] In another typical embodiment of the present application, a method for preparing the aforementioned electrode is provided, and the preparation method comprises: step S1, smelting and atomizing a high entropy alloy raw material in sequence to obtain a high entropy alloy powder; step S2, mixing the high entropy alloy powder with metal nickel powder to obtain a metal mixture; step S3, coating the metal mixture on the surface of a nickel substrate by plasma spraying to obtain a composite material; step S4, etching the surface of the composite material with a pulsed laser to form a metal layer on the surface of the nickel substrate to obtain an electrode.

[0026] Melting and atomizing the high entropy alloy raw material helps to obtain high entropy alloy powder with uniform particle size and consistent morphology. Mixing the high entropy alloy powder with metal nickel powder helps to improve the bonding force between the metal layer and the nickel substrate. The metal mixture is coated on the surface of the nickel substrate by plasma spraying, and this process can form a dense and uniform metal layer. Etching the surface of the composite material using a pulsed laser can accurately construct an etched groove structure. This process not only increases the specific surface area of ​​the electrode, provides more catalytic active sites, but also optimizes the formation of bubbles and the multiphase mass transfer process. The present application is based on melting, atomization and plasma spraying to achieve large-area cladding on the surface of the nickel substrate. This method has the advantages of simple process and short preparation cycle, and can be mass-produced.

[0027] Including but not limited to, the nickel substrate is a nickel felt with a porosity of 80% or a 46-mesh twill woven nickel mesh.

[0028] Including but not limited to, the morphology of the above-mentioned etched grooves is selected from any one or more of a periodic corrugated shape, a lattice shape, a rod array shape, an etched groove row shape, a pit shape, and a fish scale shape.

[0029] In one embodiment of the present application, in the above step S1, the smelting time is 2 to 12 hours; and / or the smelting temperature is 1500 to 2500°C; preferably, the smelting is carried out in a vacuum suspension smelting furnace; the power of the vacuum suspension smelting furnace is 50 to 500kW; and / or the vacuum leakage rate of the vacuum suspension smelting furnace is <1Pa / h; and / or the particle size of the high entropy alloy powder is 100 to 500 mesh; and / or the morphology of the high entropy alloy powder is an ellipsoid.

[0030] Preferably, the time and temperature of smelting are controlled within the above range, which helps to promote the full mixing of high entropy alloy components and the stable formation of high entropy alloy phases. Selecting to smelt in a vacuum suspension smelting furnace helps to reduce the probability of high entropy alloy being oxidized at high temperatures, helps to improve the purity of high entropy alloys, and at the same time, through the suspension smelting technology, helps to better achieve the uniform distribution of high entropy alloy elements. Preferably, the power of the vacuum suspension smelting furnace is controlled within the above range, which helps to promote the formation of high entropy alloys. Smaller particle size helps to improve the bonding force between powder and substrate during spraying, and a specific ellipsoidal shape can promote the uniform distribution of metal layer materials. Controlling the particle size of the high entropy alloy powder within the above range helps to form a dense and uniform metal layer in the subsequent plasma spraying process, thereby helping to improve the efficiency and stability of the electrode in the electrochemical reaction.

[0031] In one embodiment of the present application, in the above step S2, the mixing is ball milling mixing, and the rotation speed of the ball milling mixing is 150 to 500 rpm; and / or the ball milling mixing time is 0.5 to 10 h; and / or the particle size of the metal nickel powder is 300 to 500 mesh.

[0032] Controlling the rotation speed and time of ball milling mixing within the above range helps to improve the mixing efficiency. Controlling the particle size of the metal nickel powder within the above range helps to improve the compatibility and mixing effect of the metal nickel powder and the high entropy alloy powder. The particle size of the nickel powder matches the high entropy alloy powder, which can promote the uniform mixing of the two during the ball milling process and help reduce the risk of stratification or agglomeration caused by particle size differences. In addition, the fine particle size of the nickel powder helps to improve the bonding strength between the metal layer and the substrate and enhance the adhesion of the metal layer, thereby helping to improve the stability of the electrode.

[0033] In one embodiment of the present application, in the above step S2, the diameter of the ball milling beads for ball milling mixing is 10-30 mm, and the ball milling beads are preferably zircon beads.

[0034] In one embodiment of the present application, in the above step S2, high entropy alloy powder, metal nickel powder and ethanol are mixed and ball-milled in a wet state, the mass ratio of ethanol to high entropy alloy powder is 1:100~1, and after ball milling, air drying is carried out, the drying temperature is 100~200℃, and the drying time is 2~6h.

[0035] In one embodiment of the present application, in the above step S3, the power of plasma spraying is 30 to 65 kW; and / or, the gas for plasma spraying is H2 / Ar mixed gas, and the volume ratio of hydrogen to argon in the H2 / Ar mixed gas is 1:2 to 10; and / or, the flow rate of the H2 / Ar mixed gas is 8 to 15 L / min; preferably, the plasma spraying is vacuum plasma spraying.

[0036] Controlling the power of plasma spraying within the above range helps to fully melt the metal mixture, while reducing the probability of thermal damage to the nickel substrate and the metal layer, helping to improve the uniformity and density of the metal layer, thereby helping to improve the conductivity and mechanical stability of the electrode. Using H2 / Ar mixed gas as the process gas for plasma spraying, hydrogen can be used as a reducing agent, which helps to further optimize the surface state of the high entropy alloy during the spraying process and reduce the formation of oxides, while argon, as an inert gas, can provide a stable plasma environment while reducing the probability of oxidation of the metal layer. Controlling the volume ratio of hydrogen to argon within the above range can not only provide enough hydrogen to reduce the oxidation reaction, but also maintain the stable combustion of the plasma. Controlling the flow rate of H2 / Ar mixed gas within the above range helps to maintain the stable combustion of the plasma, while allowing the powder material to be uniformly transmitted and sprayed. The preferred vacuum plasma spraying technology can maintain an oxygen-free environment throughout the spraying process, further reducing the probability of oxidation of the high entropy alloy during the thermal spraying process, thereby helping to improve the catalytic activity and bonding force of the metal layer.

[0037] In one embodiment of the present application, in the above step S4, the power density of the pulsed laser is 5 to 100 J / cm 2 ; and / or, the wavelength of the pulse laser is 100 to 1200 nm; and / or, the frequency of the pulse laser is 5 to 100 kHz; and / or, the pulse width of the pulse laser is 10 to 2000 fs; and / or, the output laser power of the pulse laser is 1000 to 10000 mW.

[0038] Controlling the power density of the pulsed laser within the above range helps to control the depth and inner diameter of the etched groove within a suitable range, thereby helping to improve the catalytic efficiency of the electrode. Controlling the wavelength of the pulsed laser within the above range helps the interaction between the laser and the surface of the high entropy alloy to generate sufficient energy for etching of the micro-nano structure, thereby helping to improve the efficiency of etching. Higher frequencies can speed up processing and improve production efficiency, but they also require precise control to avoid overheating of the material and affecting the formation of the etched grooves. Controlling the frequency of the pulsed laser within the above range helps to improve the uniformity of the etched grooves and improve processing efficiency. Controlling the pulse width of the pulsed laser within the above range helps to provide high energy in a very short time, while forming the etched grooves, reducing the impact of heat diffusion on the surrounding materials, and helping to maintain the clarity and structural integrity of the etched grooves. Controlling the output laser power of the pulsed laser helps to control the volume ratio of the etched grooves in the metal layer within a suitable range, thereby helping to improve the catalytic activity of the electrode.

[0039] In one embodiment of the present application, the above-mentioned step S4 also includes placing the etched composite material in a saturated water vapor environment for hydroxylation treatment to obtain an electrode; preferably, the temperature of the hydroxylation treatment is 10 to 60°C; and / or, the time of the hydroxylation treatment is 0.5 to 10 hours; and / or, the protective gas in the saturated water vapor environment is selected from any one or more of nitrogen, argon and helium; and / or, the mass content of oxygen in the saturated water vapor environment is less than 0.1%.

[0040] Through the hydroxylation treatment in a saturated water vapor environment, hydrophilic hydroxyl groups are formed on the electrode surface. The presence of hydroxyl groups helps to improve the hydrophilicity of the electrode, helps to promote the contact between the electrolyte and the electrode surface, and helps to reduce the rapid oxidation of the electrode by oxygen in the air, which helps to make the electrode have long-term catalytic activity. Controlling the temperature and time of the hydroxylation treatment within the above range helps to control the mass proportion of hydroxyl groups in the metal layer within a suitable range, thereby helping to improve the catalytic activity of the electrode.

[0041] In another typical embodiment of the present application, there is provided application of the above-mentioned electrode in electrolysis of water.

[0042] The electrode of the present application has lower oxygen evolution overpotential and hydrogen evolution overpotential, and has higher catalytic activity in water electrolysis.

[0043] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] 1) Add metal ingots with equal molar ratios of Ni, Fe, Co, Cu, and Mo elements into a vacuum suspension melting furnace with a power of 200 kW, a molten state maintenance time of 6 hours, a melting temperature of 2000°C, and a vacuum leakage rate of <0.5 Pa / h; then, atomization powdering is performed under a vacuum environment, and high entropy alloy powders with a particle size of 150 to 325 meshes are screened out using 150 mesh and 325 mesh stainless steel screens, and the high entropy alloy powders have an ellipsoidal morphology;

[0046] 2) Add 2 kg of the high entropy alloy powder prepared in step 1, 0.5 kg of 325 mesh nickel powder and 0.5 kg of ethanol into a ball mill for ball milling at a speed of 200 rpm for 6 h, and select 20 mm zircon beads for ball milling; after ball milling, perform forced air drying at a drying temperature of 150° C. for 2 h to obtain a metal mixture;

[0047] 3) Selecting vacuum plasma spraying to melt-coat the metal mixture obtained in step 2 on the surface of nickel felt with a porosity of 80%, the power of vacuum plasma spraying is 45kW, the process gas for generating plasma is H2 / Ar mixed gas, the volume ratio of hydrogen to argon is 1:4, and the total flow rate of H2 / Ar mixed gas is 12L / min, to obtain a composite material;

[0048] 4) By laser etching, orderly periodic corrugated grooves are etched on the surface of the metal layer. The power density of the pulsed laser is 60 J / cm 2 , wavelength is 200nm, frequency is 30kHz, pulse width is 500fs, output laser power is 4000mW, the prepared electrode surface has periodic etched grooves, the coverage of the grooves on the metal layer surface is 90%, the width of the etched grooves is 30nm, the depth of the etched grooves is 8nm, and the spacing between adjacent etched grooves is 30nm;

[0049] 5) The material prepared in step 4 is placed in a saturated water vapor environment for surface hydroxylation treatment, the saturated water vapor environment temperature is 35°C, the protective gas is argon, the oxygen content is less than 0.01%, and the placement time is 2 hours to obtain an electrode, and the total surface hydroxyl density of the metal layer is 10.5OH / nm 2 The thickness of the metal layer is 40 μm and the specific surface area of ​​the electrode is 142 m 2 / g.

[0050] Example 2

[0051] The difference from Example 1 is that ruthenium, rhodium, palladium, osmium, iridium and platinum are used to replace Ni, Fe, Co, Cu and Mo to finally obtain an electrode.

[0052] Example 3

[0053] The difference from Example 1 is that a 46-mesh twill woven nickel mesh is used to replace the nickel felt with a porosity of 80%, and finally an electrode is obtained.

[0054] Example 4

[0055] The difference from Example 1 is that the power density of the pulsed laser is 5 J / cm 2 , wavelength is 100nm, frequency is 5kHz, pulse width is 10fs, output laser power is 1000mW, the coverage of the etched grooves on the metal layer surface is 50%, the spacing between adjacent etched grooves is 50nm, and the electrode is finally obtained with a specific surface area of ​​71m 2 / g.

[0056] Example 5

[0057] The difference from Example 1 is that the power density of the pulsed laser is 100 J / cm 2 , wavelength is 1200nm, frequency is 100kHz, pulse width is 2000fs, output laser power is 10000mW, the coverage of the etched grooves on the metal layer surface is 100%, the spacing between adjacent etched grooves is 10nm, and finally the electrode is obtained, and the specific surface area of ​​the electrode is 176m 2 / g.

[0058] Example 6

[0059] The difference from Example 1 is that the power density of the pulsed laser is 5 J / cm 2 , and finally an electrode is obtained, the width of the etched groove is 20nm, and the depth of the etched groove is 1nm.

[0060] Example 7

[0061] The difference from Example 1 is that the power density of the pulsed laser is 100 J / cm 2 Finally, an electrode is obtained, the width of the etched groove is 50nm, and the depth of the etched groove is 20nm.

[0062] Example 8

[0063] The difference from Example 1 is that the power density of the pulsed laser is 120 J / cm 2 Finally, an electrode was obtained, the width of the etched groove was 62nm, and the depth of the etched groove was 28nm.

[0064] Example 9

[0065] The difference from Example 1 is that the saturated water vapor environment temperature is 10°C, the placement time is 0.5h, and the electrode is finally obtained, and the total surface hydroxyl density of the metal layer is 4OH / nm 2 .

[0066] Example 10

[0067] The difference from Example 1 is that the saturated water vapor environment temperature is 60°C, the placement time is 10 hours, and the electrode is finally obtained, and the total surface hydroxyl density of the metal layer is 20OH / nm 2 .

[0068] Embodiment 11

[0069] The difference from Example 1 is that the saturated water vapor environment temperature is 5°C, the placement time is 0.2h, and the electrode is finally obtained, and the total surface hydroxyl density of the metal layer is 0.4OH / nm 2 .

[0070] Example 12

[0071] The difference from Example 1 is that 100-mesh and 200-mesh stainless steel sieves are used to screen out powders with a particle size of 100-200 meshes, the particle size of the metal nickel powder is 300 meshes, and finally an electrode is obtained.

[0072] Example 13

[0073] The difference from Example 1 is that 300-mesh and 500-mesh stainless steel sieves are used to screen out powders with a particle size of 300-500 mesh, the particle size of the metal nickel powder is 500 mesh, and finally an electrode is obtained.

[0074] Embodiment 14

[0075] The difference from Example 1 is that 550-mesh and 650-mesh stainless steel sieves are used to screen out powder with a particle size of 550-650 mesh, and the particle size of the metal nickel powder is 600 mesh, and finally an electrode is obtained.

[0076] Embodiment 15

[0077] The difference from Example 1 is that the mass of 325-mesh nickel powder is 2 kg, and the electrode is finally obtained.

[0078] Example 16

[0079] The difference from Example 1 is that the mass of 325-mesh nickel powder is 0.2 kg, and the electrode is finally obtained.

[0080] Embodiment 17

[0081] The difference from Example 1 is that the mass of 325-mesh nickel powder is 0.1 kg, and the electrode is finally obtained.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that no laser etching is performed, and finally an electrode is obtained.

[0084] Performance Testing

[0085] The electrodes prepared in the examples and comparative examples were cut into a rectangular block with a length of 1.5 cm and a width of 1 cm, and fixed with an electrode clamp as a working electrode for oxygen evolution reaction in an alkaline electrolyte. In the three-electrode test system, the platinum wire is the counter electrode, the mercury / mercuric oxide electrode is the reference electrode, and the effective area of ​​the working electrode immersed in the electrolyte is 1 cm 2 , the test system selected 1 mol / L potassium hydroxide as the electrolyte.

[0086] The electrochemical data were tested by linear voltammetry and AC impedance method. The rate of linear voltammetry was 5 mV / s, the test potential of AC impedance was 1.53 V (vs. RHE), the AC amplitude was 10 mV, and the frequency range was 10 6 ~10 -1Hz. The electrode was applied to an AEM single cell and tested in electrolytic water to reach 1.5A / cm 2 The voltage required for the current density. The test electrode is at 100mA / cm 2 The oxygen evolution overpotential and hydrogen evolution overpotential at current density up to 1.5A / cm 2 The voltage required for the current density and the test results are shown in Table 1.

[0087] Table 1

[0088]

[0089]

[0090] It can be seen from Table 1 that the electrode of Example 1 has a 2 The oxygen evolution overpotential under current density is 209mV, and the hydrogen evolution overpotential is 89mV, which are respectively better than 370mV of commercial noble metal oxygen evolution catalyst IrO2 and 123mV of hydrogen evolution catalyst Pt / C; the electrode of Example 1 reaches 1.5A / cm in the water decomposition test. 2 The voltage required for the current density is only 1.78V, which is better than the 2.08V of the membrane electrode made of commercial IrO2 and Pt / C.

[0091] Compared with Example 1, Example 2 uses precious metals as high entropy alloy components, and has better catalytic performance, which proves the versatility of the synthesis method for the selection of metal elements of catalytic materials; Example 3 can also prepare electrodes with similar results after replacing the substrate, which proves the versatility of the synthesis method for the selection of electrode substrates; In Example 4, the pulsed laser has a low degree of surface etching, and the surface has fewer orderly etched grooves, which has a low performance enhancement effect; In Example 5, the pulsed laser has a high degree of surface etching, but it also leads to poor orderliness of the etched groove structure, which has a low performance enhancement effect; In Example 6, Low laser power leads to shallow surface groove depth, weak effect on improving the exposed active sites on the surface, and low performance; in Example 7, high laser power leads to large surface groove width, and also destroys order, so the effect of improving the flow of surface micro-nanoscale electrolyte and bubble overflow is poor, and the performance is low under comprehensive factors; in Example 8, under the condition of excessively high laser power, melting occurs on the surface of the material, the morphology of the groove is disordered and the size is too large, which is not helpful for improving the specific surface area, so the performance is seriously reduced; in Example 9, the degree of hydroxylation on the surface of the material is insufficient, and the hydrophilicity of the electrode is poor; In Example 10, the degree of hydroxylation on the material surface is too high, covering too many active sites, affecting the catalytic reaction process; in Example 11, the degree of hydroxylation on the material surface is too low, the electrode surface is not hydrophilic, and the mass transfer process between the electrode and the electrolyte is limited; in Example 12, the particle size of the high entropy alloy powder is too large, resulting in a low degree of melting during the plasma spraying process, making the substrate surface coating not dense and with many gaps; in Example 13, the particle size of the high entropy alloy powder and the nickel powder is too small, resulting in poor fluidity during the powder feeding process of vacuum plasma spraying, discontinuous spraying flame, affecting the coating density and uniformity; in Example 14, the particle sizes of the high entropy alloy powder and the nickel powder are too small, resulting in poor process matching with the vacuum plasma spraying process and poor coating cladding effect; in Example 15, the nickel powder used for bonding is added too much, resulting in a decrease in the content of the high entropy alloy as a catalytic active component in the coating and a decrease in catalytic activity; in Example 16, the nickel powder used for bonding is added too little, resulting in weak bonding strength of the coating and easy fall-off of the high entropy alloy component on the electrode surface; in Example 17, the nickel powder used for bonding is added too little, and the high entropy alloy component on the electrode surface is extremely easy to fall off, resulting in a decrease in performance.

[0092] Compared with Example 1, the lack of laser etching in Comparative Example 1 results in a small specific surface area of ​​the electrode and fewer exposed catalytic active sites. Therefore, the advantage of the high intrinsic catalytic activity of the high entropy alloy cannot be brought into play, resulting in poor catalytic performance.

[0093] Figure 1 is a SEM image of the electrode in Example 1 of the present application, from Figure 1 It can be seen that laser etching can form an etched groove structure with regular morphology.

[0094] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0095] The presence of etched grooves on the surface of the metal layer helps to increase the specific surface area of ​​the electrode and provide more active sites for the electrolysis of water. High entropy alloys have abundant active sites due to their unique lattice structure, and the presence of etched grooves further increases the number of these active sites, thereby helping to improve the catalytic activity of the electrode. In addition, the etched groove structure is conducive to the formation and detachment of hydrogen and oxygen bubbles, reduces the residence time of bubbles on the electrode surface, and optimizes the mass transfer process of bubbles, thereby helping to improve the efficiency of water electrolysis. The presence of metallic nickel not only helps to improve the bonding force between the metal layer and the nickel substrate, but also makes the metal layer more compact, which helps to reduce the shedding of the metal layer during the electrolysis process and improves the long-term stability of the electrode. Controlling the coverage of the etched grooves on the surface of the metal layer within the above range helps to further increase the catalytic active sites on the electrode surface while maintaining the stability of the electrode structure, thereby helping to improve the catalytic activity of the electrode.

[0096] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electrode, characterized in that: The electrode includes a nickel substrate and a metal layer coated on the surface of the nickel substrate. The material of the metal layer includes metal nickel and a high entropy alloy. A plurality of etched grooves are distributed on the surface of the metal layer away from the nickel substrate. The coverage of the etched grooves on the surface of the metal layer is 50-100%.

2. The electrode according to claim 1, characterized in that The width of the etching groove is 20-50 nm and the depth is 1-20 nm; and / or, the spacing between adjacent etching grooves is 10-50 nm; and / or, a plurality of etching grooves are distributed in an array; and / or, the surface of the metal layer also contains hydroxyl groups, and the hydroxyl density in the total surface of the metal layer is 4-20 OH / nm 2 ; and / or, the thickness of the metal layer is 20 to 100 μm; and / or, the mass ratio of the metal nickel to the high entropy alloy is 10 to 100:100; and / or, the specific surface area of ​​the electrode is 40 to 180 m 2 / g.

3. The electrode according to claim 1 or 2, characterized in that The elements in the high entropy alloy are selected from any five or more of titanium, vanadium, chromium, manganese, nickel, iron, cobalt, copper, zinc, molybdenum, ruthenium, rhodium, palladium, osmium, iridium and platinum.

4. A method for preparing the electrode according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, melting and atomizing the high entropy alloy raw material in sequence to obtain high entropy alloy powder; Step S2, mixing the high entropy alloy powder with metal nickel powder to obtain a metal mixture; Step S3, coating the metal mixture on the surface of the nickel substrate by plasma spraying to obtain a composite material; Step S4, using a pulsed laser to etch the surface of the composite material to form a metal layer on the surface of the nickel substrate, thereby obtaining the electrode.

5. The preparation method according to claim 4, characterized in that: In the step S1, the smelting time is 2 to 12 hours; and / or the smelting temperature is 1500 to 2500°C; Preferably, the smelting is carried out in a vacuum suspension smelting furnace; the power of the vacuum suspension smelting furnace is 50-500kW; and / or the vacuum leakage rate of the vacuum suspension smelting furnace is <1Pa / h; And / or, the particle size of the high entropy alloy powder is 100-500 mesh; and / or, the morphology of the high entropy alloy powder is an ellipsoid.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the mixing is ball milling mixing, the rotation speed of the ball milling mixing is 150 to 500 rpm; and / or the time of the ball milling mixing is 0.5 to 10 h; And / or, the particle size of the metal nickel powder is 300-500 meshes.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S3, the power of the plasma spraying is 30 to 65 kW; and / or the gas for the plasma spraying is a H2 / Ar mixed gas, and the volume ratio of hydrogen to argon in the H2 / Ar mixed gas is 1:2 to 10; and / or the flow rate of the H2 / Ar mixed gas is 8 to 15 L / min; preferably, the plasma spraying is vacuum plasma spraying.

8. The preparation method according to any one of claims 4 to 7, characterized in that In step S4, the power density of the pulsed laser is 5 to 100 J / cm 2 ; and / or, the wavelength of the pulse laser is 100 to 1200 nm; and / or, the frequency of the pulse laser is 5 to 100 kHz; and / or, the pulse width of the pulse laser is 10 to 2000 fs; and / or, the output laser power of the pulse laser is 1000 to 10000 mW.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The step S4 further includes placing the etched composite material in a saturated water vapor environment for hydroxylation to obtain the electrode; Preferably, the temperature of the hydroxylation treatment is 10 to 60° C.; and / or, the time of the hydroxylation treatment is 0.5 to 10 h; and / or, the protective gas in the saturated water vapor environment is selected from any one or more of nitrogen, argon and helium; and / or, the mass content of oxygen in the saturated water vapor environment is less than 0.1%.

10. Use of the electrode according to any one of claims 1 to 3 in electrolysis of water.

Citation Information

Patent Citations

  • Electrolyzed water oxygen evolution catalyst coating material as well as preparation method and application thereof

    CN116377500A

  • Preparation method of hydrogen evolution electrode and alkaline electrolytic cell

    CN117004984A

  • Alkaline electrolysis water membrane electrode assembly and preparation method thereof

    CN117867550A

  • High-entropy alloy electrolytic water catalytic hydrogen evolution material and preparation method thereof

    CN117966191A

  • High-corrosion-resistance hydrogen evolution electrode material as well as preparation method and application thereof

    CN118461047A